Rethinking competitiveness: important attributes for a successful scuba diving destination. Issue 3 (3rd July 2017) - Queiroz Neto, Ambrozio; Lohmann, Gui; Scott, Noel; Dimmock, Kay
ABSTRACT: Competitive advantage arises from a superior value that, rather than delivered by suppliers, is co-created by tourists. Using a set of destination competitiveness attributes, this study investigates the importance of destination competitiveness attributes in a 'hypothetical successful scuba diving destination' from the perspective of scuba diving tourists. Further, this study also investigates to what extent level of experience as a scuba diver influences the importance given to destination competitiveness attributes. An online survey ( n = 712) identified 10 underlying factors (groups of attributes): diving operations, risk perception, diving conditions, price, destination management, big wildlife encounters, diving training, tech diving, general tourist attraction and visa policy. Furthermore, this research established that the attributes related to diving operations are the most important and that divers with different levels of experience value differently 6 of the 10 destination competitiveness factors. This research presents evidence that destination competitiveness may be explored through unique demands in tourism niches (and within niches) rather than generally for a destination.